2010
DOI: 10.4317/jced.2.e113
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal study of age and order of eruption of primary teeth in Indian children

Abstract: Objective: To determine the chronological eruption parameters of primary teeth in Indian children. Study Design: A longitudinal study consisting of 135 healthy children (74 boys and 61 girls) attending three child health centres in the city of Hyderabad, India were randomly selected and followed from the emergence of the first to the last tooth. Ages and order of tooth eruption were studied for both genders. Results: Boys showed tendency towards earlier eruption for all teeth except maxillary second molar and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 12 publications
2
12
0
Order By: Relevance
“…The Indian population is made up of many races and ethnicities. Similar findings have been reported by GunaShekhar and Tenny, who found that boys had earlier eruption compared to girls, and the study population experienced delayed eruption of primary teeth when compared to their counterparts in other populations . Because the Indian population is multiethnic in nature, the result warrants the need for a study to be conducted on a larger scale, controlling for the effect of different ethnic backgrounds and socioeconomic conditions.…”
Section: Discussionsupporting
confidence: 87%
“…The Indian population is made up of many races and ethnicities. Similar findings have been reported by GunaShekhar and Tenny, who found that boys had earlier eruption compared to girls, and the study population experienced delayed eruption of primary teeth when compared to their counterparts in other populations . Because the Indian population is multiethnic in nature, the result warrants the need for a study to be conducted on a larger scale, controlling for the effect of different ethnic backgrounds and socioeconomic conditions.…”
Section: Discussionsupporting
confidence: 87%
“…Very few studies were carried out in the past on the eruption time of teeth in the Indian population. 5 - 8 The studies done by Tendon 9 and Gunashekhar and Tenny 8 showed differences in the eruption of deciduous dentition, and the study done by Gupta et al 10 showed differences in the eruption of permanent dentition in a south Indian population as compared with the data given by Logan and Kronfeld 4 that was based on Western population. These findings strongly suggest that racial differences between the two populations is the main factor underlying the variations in eruption timings.…”
Section: Discussionmentioning
confidence: 93%
“…The catch-up weight growth is the compensatory weight gain and above normal standards for specific age between birth and 24 months. Considering the catch up and the delay in the dental eruption in children with low birth weight is even more evident until 24 months of age, 11,29 opting to control the child's covariate age, even if the child did not behave as a modifier effect in the analysis. Higher magnitude of positive associations were found among children aged up to 24 months.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] The knowledge on the normal timing of tooth eruption ranges from the intrauterine life up to 30 months, it has clinical relevance to diagnose various locations and systemic conditions that may affect this process. [1][2]4,6,[9][10][11][12][13][14][15][16][17] The variation in the chronological dental eruption is dependent of multiple genetic and environmental factors and none of them acts individually, there is an inter-relation among themselves during the development of deciduous teething, such as race, gender, systemic conditions, environmental conditions, socioeconomic level, maternal breastfeeding, infant nutritional status and physical development. 1,18 Nutritional factors influence the odontogenesis and the eruption of the teeth.…”
Section: Introductionmentioning
confidence: 99%